Myocardial Infarction with Non-Obstructive Coronary Arteries: Contemporary Diagnostic and Management Approaches - T. H. Hoang; P. V. Lazarev; V. V. Maiskov; A. I. Meray; Zh. D. Kobalava (Столичная издательская компания, 2020)
Myocardial infarction with non-obstructive coronary arteries (MINOCA) is diagnosed in the absence of anatomically significant stenoses (<50% of lumen diameter) on coronary angiography and characterized by heterogeneity of etiologic factors. Recently, the mechanisms of MINOCA as well as the performance of diagnostic algorithms and therapeutic strategies have been extensively studied. The purpose of this review is to reflect the current concepts regarding the etiology and pathogenesis of MINOCA, diagnostic work-up methods and individualized treatment approaches. The article covers contemporary epidemiologic data, demographic and clinical patients' characteristics and principal causes of MINOCA. We discuss aspects of disease definition and classification of related conditions involving troponin increase in the presence of normal coronary arteries. The importance of management strategy personalization for individual patients is stressed alongside stratification of risks of recurrent cardiovascular events. This review reflects key points from international consensus statements published by leading experts and suggests promising directions for future research.